Desain Alat Pembuat Pelet Limbah Sayuran Bagi Peternak Ikan Lele - Laras Rihadatul Aisy; Wildan Aulia (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
There are two types of catfish feed, namely pellets and vegetable feed. Vegetable waste can be used as catfish feed because it still contains the nutrients needed by catfish. Processing vegetable waste into catfish feed consists of several processes, including sorting, washing, chopping, drying, mixing, and forming. Currently, vegetable feed is still made manually with simple tools so that it takes a long time to process, especially for small-scale catfish breeders. The existing pellet-processor is still on an industrial scale which is not suitable for small-scale catfish breeders. The data were obtained from field surveys and interviews. The data were analyzed through the research board analysis method. The results of the analysis become a flow scheme for making feed with the designed tools. The design process includes configuration studies, anthropometric and ergonomic studies, and physical form conducted through analytical prototyping methods. The success of the product is evaluated through a comparison of several variables related to product functions between existing products/tools and the designed product. The design results show an increase in the productivity of making pellets from vegetable waste but the washing and sorting process cannot be accommodated by the tool. Keywords: pellets processor, vegetable waste, catfish breeder